Proceedings of the 2010 Winter Simulation Conference 2010
DOI: 10.1109/wsc.2010.5679009
|View full text |Cite
|
Sign up to set email alerts
|

Lessons learned from utilizing discrete-event simulation modeling for quantifying construction emissions in pre-planning phase

Abstract: Construction operations have a tremendous impact upon both the environment and public health due to the generation of significant amounts of airborne emissions, including greenhouse gases and other traditional criteria air pollutants. Quantifying emissions in the pre-planning phase of construction operations is the first step in identifying mitigation opportunities. The authors therefore have quantified construction emissions produced by various types of construction operations through the use of discrete-even… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Guggemos and Horvath reported that these three operations account for 83% of the overall construction phase emissions of the structure studied in their work [104,113]. Several previous studies have focused on quantifying and minimizing the environmental impacts of earthmoving operations through optimizing operational parameters such as fleet size [114][115][116]. Kaboli and Carmichael showed that for earthmoving operations, placing the focus on minimizing costs could also lead to minimizing the carbon emissions associated with the process [117].…”
Section: Construction Optimization Strategiesmentioning
confidence: 99%
“…Guggemos and Horvath reported that these three operations account for 83% of the overall construction phase emissions of the structure studied in their work [104,113]. Several previous studies have focused on quantifying and minimizing the environmental impacts of earthmoving operations through optimizing operational parameters such as fleet size [114][115][116]. Kaboli and Carmichael showed that for earthmoving operations, placing the focus on minimizing costs could also lead to minimizing the carbon emissions associated with the process [117].…”
Section: Construction Optimization Strategiesmentioning
confidence: 99%
“…The application of DES in estimating emissions gives several benefits such as getting reliable statistical results on the equipment activity. It can be used to compare construction emissions from other scenarios and to aid the designing of the construction operation which has few emissions [11]. In addition, DES can simulate a project or operation by running chronologically occurring events [2].…”
Section: Discrete Event Simulationmentioning
confidence: 99%
“…Ahn et al (2010) Lewis et al (2009b) discussed the challenges associated with quantification of non-road vehicle emissions and proposed a new research agenda that specifically focuses on air pollution generated by construction equipment. Artenian et al (2010) demonstrated that lowering emissions could be achieved through an intelligent and optimized GIS route planning for offsite transportations of construction equipment.…”
Section: Background and Related Workmentioning
confidence: 99%